Sociodemographic determinants and assessment of anti-α-Gal IgG titers in head and neck cancer patients - Lopes, Dayse Marcielle de Souza; Gomes, Clarissa Fernandes; Durães, Cristina Paixão; Fonseca, Larissa Lopes; Costa, Sarah Patrícia Souza; Guimarães, André Luiz Sena; Arrudas, Sônia Ribeiro; Lacerda, Guilherme Araújo; Finn, M. G.; de Carvalho, Sílvio Fernando Guimarães; Moura, Ana Paula Venuto; Marques, Alexandre Ferreira (Frontiers in Oncology, 2025)
Head and neck cancer (HNC) remains a pressing global health challenge, particularly in regions with lower socioeconomic status, where risk behaviors such as tobacco use and alcohol consumption are prevalent. Despite advances in treatment, reliable biomarkers for the early detection and monitoring of HNC remain lacking. The α-Gal carbohydrate epitope, absent in humans but present in other mammals, has garnered interest due to the natural presence of anti-α-Gal antibodies in the human immune repertoire, comprising approximately 1% of total circulating IgG. We investigated the role of anti-α-Gal IgG as a potential biomarker by performing ELISA on serum samples from a cohort of 11 patients diagnosed with squamous cell carcinoma (SCC) of the head and neck. Eight were older male patients, most of whom lived in rural areas and engaged in manual occupations. High rates of tobacco (81.8%) and alcohol consumption (63.6%) were observed, in line with established risk factors for HNC. These individuals showed significantly elevated anti-α-Gal antibody titers compared to non-cancer controls. Chemotherapy with cisplatin did not markedly affect antibody levels, suggesting consistent immune reactivity across treatment status. These results suggest that anti-α-Gal antibodies may serve as promising biomarker candidates in HNC and warrant further investigation to clarify their potential diagnostic and immunotherapeutic applications.